Modeling the Hygrothermal Performance of Selected North American and Comparable European Wood-Frame House Walls - Pásztory Zoltán (ENERGY AND BUILDINGS, 2012)
In North America, the exterior finish of wood-frame house walls usually consists of a siding, a water resistive barrier, and an oriented strandboard (OSB) sheathing. In Europe, the exterior finish uses the External Thermal Insulation Composite System attached to a gypsum board sheathing. This study was performed to compare the hygrothermal performance of American and European walls by using a finite-element model. Analysis showed that the European wall has better thermal performance mainly because of the heat-insulating ability of the expanded polysterene (EPS) layer. But when the EPS was reduced to the same thickness as the siding used in American construction, the thermal performance of the European wall did not fare any better than the American structure. The resistance of the European wall to moisture damage was also better than the American walls. One reason for this is the high diffusion resistance of the EPS. But this same high diffusion resistance works to the detriment of an Exterior Insulation Finish System (EIFS) wall if water is able to infiltrate the structure. When water leakage is present, the water content of the OSB in the EIFS wall reaches levels that make it vulnerable to mold growth and fungal decay.